The Biosafety Protocol and its SocioEconomic Consequences - Müller, Frank G. (2002)
Biotechnology (BT) is a major source of numerous socio-economic and ecological changes and consequences as we are entering the 21st century. The public is almost daily confronted with conflicting stories that encompass the entire spectrum from BT being proclaimed as humankind's saviour to it being the cause of our ultimate environmental destruction. Governments have difficulties designing appropriate policies to regulate all aspects of BT from research protocols, to testing, to protection for intellectual property, to licensing for release into the environment, for food safety and for international trade.Given that there is a certain level of environmental uncertainty associated withthe products of BT in addition to the possibilities of negative impacts arising from trans-boundary movements of genetically modified organisms (GMO), the urgency for an international agreement to regulate trade in GMOs was recognized. The Biosafety Protocol is such an international environmental agreement that is charged with devising a comprehensive international regulatory approach to the protection of biodiversity and to establish rules to manage the environmental risks of trans-boundary movements of GMOs.The Protocol has major implications both for the technology addressed in the Protocol and for international trade. lt is the first major international agreementto use the "precautionary principie" explicitly to allow the restriction of trade in products because they were produced using a specific technology, namely BT. This paper intends to provide a critica! socio-economic assessment of the central issues addressed in the Protocol in regards to agro biotechnology and biodiversity.